Motor cortex repetitive transcranial magnetic stimulation in major depressive disorder - A preliminary randomized controlled clinical trial - Hu, Yu-Ting; Hu, Xi-Wen; Han, Jin-Fang; Zhang, Jian-Feng; Wang, Ying-Ying; Wolff, Annemarie; Tremblay, Sara; Hirjak, Dusan; Tan, Zhong-Lin; Northoff, Georg (Journal of affective disorders, 2024)
Background - Repetitive transcranial magnetic stimulation (rTMS) at left dorsolateral prefrontal cortex (lDLPFC) is commonly used in major depressive disorder (MDD), even though its therapeutic efficacy is limited. Given that many MDD patients show psychomotor retardation, we aim to examine whether the left motor cortex (lMC) as a novel rTMS target would provide effective and well-tolerated treatment as being comparable to lDLPFC-rTMS. - Methods - In this prospective double-blind randomized single-center study, 131 MDD patients were randomly assigned to the lDLPFC or lMC group and were treated with 10 Hz rTMS (90 % motor threshold) applied twice daily for 4000 pulses continuously over five days. The primary endpoint was the Hamilton Depression Scale (HAMD) total score change after treatment. - Results - After the five-day rTMS treatment, there was no significant difference in both HAMD reduction rate (lDLPFC 59.3 % ± 20.4 %, lMC 51.3 % ± 26.3 %, P = 0.10) and adverse effects (P = 0.79) between 48 (73.8 %) lMC subjects and 51 (77.3 %) lDLPFC subjects. Furthermore, the lMC study group showed stable HAMD scores at follow-up compared to their endpoint scores (P = 0.08). - Limitations - Sham-control group was not included and the sample size was small. Therefore, our results should be seen as exploratory and preliminary. - Conclusions - The preliminary good therapeutic response, comparability, and tolerability of lMC-rTMS suggest lMC a potential and more easily accessible rTMS target. Together, our findings raise the possibility of symptom-specific rTMS in motor cortex (psychomotor retardation) or lDLPFC (cognitive deficits). This warrants larger clinical trials of rTMS in MDD with symptom-specific stimulation targets.